Does cerebral oximetry always measure brain tissue oxygen saturation? An anatomical study utilizing computed tomography - Rotem Naftalovich; Darrick Chyu; John T Denny; Aysha Hasan; Enrique J Pantin (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: to quantify the scalp-cortex distance and determine its variation among patients. We hypothesized that in a significant number of patients, this distance is greater than the maximum penetration depth of current cerebral oximeters. Material and Methods: A retrospective anatomic study using transverse head CT images selected randomly from 102 patients over the age of 18 years without brain swelling, intracranial mass effect, or brain hemorrhage. Scalp-cortex distances were determined at two separate locations along the craniocaudal axis; most cephalad to the frontal sinus (I0) and also 2 cm cephalad to that location (I2). Multiple measurements were obtained bilaterally at 1, 3, 5, 7, and 9 cm from midline. Results: The average scalp-cortex distance was 14.3 mm and 15 mm at I0 and I2 respectively. Distances varied more in I2 than in I0; from the measurements, 12.8% vs. 6.8% were over 20 mm, 4.4% vs. 2.2% over 25 mm, 1.1% vs. 0.6% over 35 mm and 0.6% vs. none over 40 mm at I2 and I0, respectively. 1.5% of the measurements at I2 were over 30 mm. Conclusion: Cerebral oximetry manufacturers all claim to measure cerebral tissue up to a depth of 20-25 mm; 20 mm with the EQUANOX and INVOS compared with 25 mm with the FORE-SIGHT. Scalp-cortex distance is within 25 mm in more than 95% of patients. However, even with the probe placed as per the manufacturer's recommendations, in a small but significant subset of patients, this distance is greater than the maximum penetration depth of current cerebral oximeters and hence may not reflect actual brain tissue oxygen saturation.